The Teaching of ports and adapted physical education to the mentally retarded children, Division of City School Manila - Nohay, Lourdes M. (Manila : National University, 1999)
The effectiveness of any program depends upon the attitudes and perceptions of the persons involved, because it greatly influences their performance. Therefore, it is necessary to assess and analyze such attitudes and perceptions in order that improvements and modifications are made.
Title page -- Approval Sheet -- Acknowledgement -- Dedication -- Table of contents -- List of tables -- Chapter 1. The Problem and its setting -- Chapter 2. Review of related literature and studies -- Chapter 3. Research Design and Methodology -- Chapter 4. Presentation, Analysis, and Interpretation of Data -- Chapter 5. Summary, Conclusion, and Recommendation -- Bibliography -- Appendices -- Curriculum Vitae.
Research Method : Descriptive Method.
Includes bibliographical references.